R-loop formation contributes to mTORC1 activation-dependent DNA replication stress induced by p53 deficiency - Li Xiaolei; Yang Cheng; Zhang Xiaohui; Wang Feiyang; Sun Longhua; Zhang Wei; Xu Xinping (Acta Biochimica et Biophysica Sinica)
DNA replication stress is a significant contributor to spontaneous DNA damage and genome instability. While the impact of p53 deficiency on increasing DNA replication stress is known, the specific molecular mechanism underlying this phenomenon remains poorly understood. This study explores how p53 deficiency induces DNA replication stress by activating mTORC1 through R-loop formation, which is facilitated by the upregulation of RNR. Research has shown that p53 deficiency results in increased γH2AX expression and a higher mutation rate in the HPRT gene. Interestingly, these effects can be alleviated by rapamycin, an mTORC1 inhibitor. Additionally, rapamycin reduces the abundance of R-loop structures in p53KO cells, which is linked to mTORC1’s regulation of ribonucleotide reductase (RNR) level. These findings suggest that p53 deficiency-induced DNA replication stress relies on mTORC1 activation, with the upregulation of RNR expression and R-loop formation. Overall, this study underscores the importance of R-loops in mTORC1 activation-dependent DNA replication stress triggered by p53 deficiency.